Dissecting the role of adducin in the axonal cytoskeleton - Rodrigues, Joana Nogueira (2015)
The neuronal cytoskeleton is an interconnected network of filamentous polymers, having in its constitution three major components: actin, microtubules and intermediate filaments. Up to the discovery of axon actin rings, the neuronal actin cytoskeleton has gained relevance. Still, the molecular details of the regulation of the actin cytoskeleton in neurons are largely unknown. Helping in the actin cytoskeleton regulation and maintenance, there is adducin. Adducin is organized in heterotetamers of heterodimers which comprises α/β and α/γ subunits. In the nervous system, the depletion of α subunit results in an almost complete absence of functional adducin. Given this, α-adducin KO mice arose as relevant models to study the role of this protein in actin cytoskeleton. Results from our group showed that α-adducin KO mice develop progressive axon enlargement and degeneration. As defects in axonal transport have been related to axon enlargement, we determined the importance of adducin in the axonal cytoskeleton and, more specifically, in axonal transport. Although no differences were found in the retrograde transport of CTB in the optic nerve, the lack of adducin resulted in a decreased speed of axonal transport of mitochondria and lysosomes. Several neurodegenerative disorders have been associated with axonal transport deficits and, consequently, with alterations in MT-based transport. Although no differences were found in the levels of acetylated and de-tyrosinated tubulin, the levels of tyrosinated tubulin were significantly decreased in α-adducin KO brains, suggesting a less dynamic status of the MT cytoskeleton in the absence of adducin. Besides differential PTMs of tubulin the decreased axonal transport speed may result from the decreased levels of dynein and kinesin in α-adducin KO mice. Lastly, we hypothesized that adducin might be involved in the organization and/or plasticity of the AIS that requires actin dynamics. In α-adducin KO animals, although the AIS forms normally, neurons do not have the ability to relocate it in response to chronic depolarization. Still, the specific role of actin and its associated proteins, like adducin, in this process remains unclear. In sum, with this Thesis we contributed to understand the relevance of the actin in cytoskeleton, more specifically, of the actin-binding protein adducin in neuron biology.